Tackling Paradoxes and Double Binds for a Healthier Workplace: Insights from the Early COVID-19 Responses in Quebec and Ontario - Daniel Côté; Amelia León; Ai-Thuy Huynh; Jessica Dubé; Ellen MacEachen; Pamela Hopwood; Marie Laberge; Samantha Meyer; Shannon Majowicz; Meghan K. Crouch; Joyceline Amoako (Humans, 2025)
The urgency of managing the COVID-19 health crisis in workplaces led to tensions, work overload, and confusion about preventive measures. This study presents a secondary analysis of qualitative data on paradoxes and double binds (PDBs) experienced by precarious essential workers in Canada who interacted with the public and their supervisors. Based on 13 interviews from a larger qualitative dataset, we examine how workers navigated public health recommendations and organisational demands during the pandemic. Findings reveal multiple organisational and managerial PDBs—both COVID-19-related and pre-existing—that contributed to psychological distress and compromised well-being. We argue that PDBs represent a significant occupational health hazard for precarious workers. Addressing these structural contradictions through proactive management strategies could help mitigate workplace tensions, reduce stress, and enhance resilience in both crisis situations and regular organisational contexts. Our study contributes to occupational health and safety (OHS) by underscoring the risks posed by PDBs and advocating for strategies to support vulnerable workers in navigating conflicting demands.